PEMBERIAN PUPUK HIJAU DAN MOL TERHADAP PERTUMBUHAN DAN HASIL TANAMAN KACANG TANAH (ARACHIS HYPOGEAE L) - IWAN UMBU SIWA BALLA; I MADE SUNANTRA; WAWAN APZANI (Universitas Mahasaraswati Mataram, 2019)
The purpose of this study is to determine the effect of local green manure and micro organism (MOL) on the growth and yield of Peanut Plants. This study uses an experimental method with a Completely Randomized Design consisting of 2 factors, namely green manure and local micro organisms. The treatment consisted of no fertilizer, fertilizing with green fertilizer from gamal leaves, turi, chlotalaria and Chromolaena leaves. Then there are those who do not use MOL and use MOL. Both are combined to become 10 treatments. The results showed that Green and Micro Local Organisms fertilizers significantly affected peanut yield. Cromolaena treatment showed an increase in yield of 31.37%, followed by Turi leaves 27.45%, Gamal leaves 15.69% and Chlotalaria 11.76%. Furthermore, the treatment of local micro organisms increases the yield by 14.90%.